Volume 2B: Turbomachinery 2017
DOI: 10.1115/gt2017-63358
|View full text |Cite
|
Sign up to set email alerts
|

Towards High-Order Large Eddy Simulation of Aero-Thermal Flows for Turbomachinery Applications

Abstract: The solution accuracy and computational efficiency of high order Large Eddy Simulation (LES) solvers are evaluated on two benchmark open literature blade cascade problems. The first problem concerns wake development in the T106A low pressure turbine cascade [1]. The second problem examines the effect of free-stream turbulence on heat transfer from the VKI first stage high pressure turbine vane [2]. The calculations are performed with two independently developed high order LES solvers using completely different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…the kinetic loss values were not the same. Bhaskaran et al [5] also used different solvers with structured and unstructured grids and were the first to include the upstream bars for the inflow turbulence generation in a 6-th order accurate LES of the LS89 vane. The expected result was that heat transfer is controlled by the combination of turbulence intensity and length scale at the blade leading edge axial position, an information that is seldom available in the design phase, but that can have a large impact on performance.…”
Section: High-pressure Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…the kinetic loss values were not the same. Bhaskaran et al [5] also used different solvers with structured and unstructured grids and were the first to include the upstream bars for the inflow turbulence generation in a 6-th order accurate LES of the LS89 vane. The expected result was that heat transfer is controlled by the combination of turbulence intensity and length scale at the blade leading edge axial position, an information that is seldom available in the design phase, but that can have a large impact on performance.…”
Section: High-pressure Turbinementioning
confidence: 99%
“…additional non−linear terms (5) This relates the Reynolds stress tensor τ ij to its trace 2k, strain rate tensor S ij and additional non-dimensional terms. V k ij are basis functions formed from polynomials of non-dimensional strain s ij = τ S ij and rotation rate…”
Section: Data-driven Model Development For Lpt and Hptmentioning
confidence: 99%
“…3. Note, the purple line shows the exciting potential of high-order methods and hence the re-emergence of interest in such approaches in many applications including turbomachinery [8][9][10][11][12]. Flow Classification.…”
Section: Introductionmentioning
confidence: 99%
“…Large eddy simulation [1] has received increased attention for industrial applications over the past decade for challenging vortex-dominated turbulent flows [2][3][4][5][6]. Direct numerical simulations have also been used to study interesting flow physics at low Reynolds numbers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in some cases SGS models may be detrimental to the solution quality [33][34][35][36]. In practice, implicit LES (ILES) has proved its potential for turbulent flow simulations [4,5,[37][38][39]. In the context of LES, high-order adaptive methods such as DG and FR/CPR have been shown to resolve a wider spectrum than the classical FD method, and are comparable to the CD method in terms of resolution power [40,41].…”
Section: Introductionmentioning
confidence: 99%